2020
DOI: 10.1186/s40816-020-00183-y
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic activity of Neolamarckia cadamba (Roxb.) Bosser flower extract in alloxan-induced diabetic rats

Abstract: Background Various parts i.e., stem bark, leaf, root and flower of Neolamarckia cadamba (Roxb.) Bosser has been extensively used by traditional practitioners to treat all types of diabetes. Our present study investigated the antidiabetic property of the extract from its flower and evaluated its traditional use for diabetes. Results Phenolic contents were found to be higher in the methanol soluble fraction (MESF) (228.16 ± 0.32 GAE/g of sample) while flavonoids were greater in quantity in the chloroform solubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…According to Tarigan et al, (in Rabha, 2021), Chinese betel leaf plants contain chemical compounds belonging to the glycosides, flavonoids, tannins and steroid/triterpenoid groups. This is in line with Nurhaliza's research (in Munira et al, 2020) who added that the largest class of compounds found in Chinese betel nut are flavonoids. According to Angelina et (in Momin & Yeligar, 2019), the Chinese betel plant (Peperomia pellucida L.) contains alkaloids, flavonoids, saponins, tannins and triterpenoids (Slavova & Karanasios, 2018).…”
Section: Chinese Betel Nut (Peperomia Pellucida L) Phytochemicalssupporting
confidence: 90%
“…According to Tarigan et al, (in Rabha, 2021), Chinese betel leaf plants contain chemical compounds belonging to the glycosides, flavonoids, tannins and steroid/triterpenoid groups. This is in line with Nurhaliza's research (in Munira et al, 2020) who added that the largest class of compounds found in Chinese betel nut are flavonoids. According to Angelina et (in Momin & Yeligar, 2019), the Chinese betel plant (Peperomia pellucida L.) contains alkaloids, flavonoids, saponins, tannins and triterpenoids (Slavova & Karanasios, 2018).…”
Section: Chinese Betel Nut (Peperomia Pellucida L) Phytochemicalssupporting
confidence: 90%
“…The Indian tribals and villagers have been using the bark, leaf, flower and fruit of N. cadamba (Roxb.) in various traditional medicinal preparations for treating various ailments including infections, uterine disorders, skin diseases, inflammation, diarrhea, anemia, leprosy, dysentery, stomatitis, diabetes, anemia, sour throat, fever and cough [1][2][3][4][5]. N. cadamba has been placed among the useful tropical plants [6].…”
Section: Introductionmentioning
confidence: 99%
“…3 Despite of having scientific advancement and globalization, medicinal plant based drug discovery is still playing a significant role in the exploration of various pharmacological activities and the discovery of new drugs. 4 In fact, phytomedicines, nutraceuticals, herbal medicines and plant-based different preparations in various dosage forms are extensively investigated by the researchers, herbal and nutraceutical industries aiming to the discovery and development of effective and safe complementary and alternative therapies for the development of medicaments against diabetes, 5 8 cancer, 9 11 autoimmune and immunocompromised conditions, 12 18 inflammation and infectious diseases, 19 21 hyperlipidemia 22 , 23 and neurological and adaptogenic problems 24 due to the limitations of conventional drugs, because of the development of drug resistance and adverse effects and chronic toxicities in long term treatment.…”
Section: Introductionmentioning
confidence: 99%